Population Pharmacokinetic/Pharmacodynamic Modeling to Assist Dosing Schedule Selection for Dovitinib. (24th January 2013) - Wang, Xiaofeng; Kay, Andrea; Anak, Oezlem; Angevin, Eric; Escudier, Bernard; Zhou, Wei; Feng, Yilin; Dugan, Margaret; Schran, Horst
Abstract Dovitinib is an oral multitargeted kinase inhibitor with potent activity against receptors for vascular endothelial growth factor, platelet‐derived growth factor, and basic fibroblast growth factor. Initial phase 1 to 2 studies of dovitinib using a continuous daily dosing schedule has shown that dovitinib exhibits a prolonged and overproportional increase in dose and exposure relationship above 400 mg/d. To address this, intermittent dosing schedules were explored using a model‐based approach. A semi‐mechanistic population pharmcokinetic/pharmacodynamic (PD) model was developed from 4 dovitinib phase 1 studies with daily dosing schedules. Autoinduction of cytochrome P450 1A (CYP1A) responsible for dovitinib metabolism was described using an indirect response model. Simulation of dovitinib plasma concentration profiles following 4 intermittent dosing schedules suggested that intermittent dosing could prevent prolonged drug accumulation. Based on the simulated plasma profiles, PD response, and patient compliance, a 5‐days‐on/2‐days‐off intermittent dosing schedule was selected for a phase 1 to 2 clinical study. The observed dovitinib plasma concentrations in this study confirmed the model predictions. Furthermore, dovitinib was well tolerated, and antitumor activity was observed as well in this new study. The 5‐days‐on/2‐days‐off dosing schedule is currently used in a dovitinib registration trial and other clinical trials.